2022
DOI: 10.3390/jox12030013
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of the Endocrine-Disrupting Effects of Disinfection Byproducts

Abstract: Since 1974, more than 800 disinfection byproducts (DBPs) have been identified from disinfected drinking water, swimming pool water, wastewaters, etc. Some DBPs are recognized as contaminants of high environmental concern because they may induce many detrimental health (e.g., cancer, cytotoxicity, and genotoxicity) and/or ecological (e.g., acute toxicity and development toxicity on alga, crustacean, and fish) effects. However, the information on whether DBPs may elicit potential endocrine-disrupting effects in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 108 publications
(168 reference statements)
0
2
0
Order By: Relevance
“…For potential endocrine disrupting effects of DBPs, previous research focused mainly on determining the effects of some DBPs on various kinds of proteins and cell lines from humans and other mammals. For example, the results from in vitro assay documented that DBPs could interfere hormone transporters (i.e., human transthyretin (hTTR) and human serum albumin), activate/inhibit hormone receptors such as human or rat estrogen receptor, human androgen receptor, ,, peroxisome proliferator-activated receptor gamma (PPARγ), , and retinoid X receptor, and inhibit follicle growth and steroidogenesis in mouse ovarian antral follicles . The in vivo study also found that iodoacetic acid (IAA) could disrupt the rat thyroid system and elicit reproductive and developmental toxicity .…”
Section: Introductionmentioning
confidence: 99%
“…For potential endocrine disrupting effects of DBPs, previous research focused mainly on determining the effects of some DBPs on various kinds of proteins and cell lines from humans and other mammals. For example, the results from in vitro assay documented that DBPs could interfere hormone transporters (i.e., human transthyretin (hTTR) and human serum albumin), activate/inhibit hormone receptors such as human or rat estrogen receptor, human androgen receptor, ,, peroxisome proliferator-activated receptor gamma (PPARγ), , and retinoid X receptor, and inhibit follicle growth and steroidogenesis in mouse ovarian antral follicles . The in vivo study also found that iodoacetic acid (IAA) could disrupt the rat thyroid system and elicit reproductive and developmental toxicity .…”
Section: Introductionmentioning
confidence: 99%
“…Whereas toxicological data on fish have also included histological as well as biochemical adverse effects (Lata et al, 2023). Regarding the endocrine disruption of DBPs, some studies have investigated the effects of DBPs in fish (Chaves et al, 2020;Wang et al, 2022), including endocrine disrupting effects on medaka fish estrogen receptor a (Sui et al, 2022). However, limited information exists on their effects on zebrafish estrogen receptor a (zERa) (Lee et al, 2023).…”
Section: Introductionmentioning
confidence: 99%